1995
DOI: 10.1016/s0022-5223(05)80025-x
|View full text |Cite
|
Sign up to set email alerts
|

Fourteen-year experience with homovital homografts for aortic valve replacement

Abstract: Two hundred seventy-five unprocessed, viable homograft ("homovital") aortic valves were used for aortic valve replacement in patients aged 1.5 to 79 years (mean 45.8 +/- 19 years) with maximum follow-up of a 14-year period (mean 4.8 years). Ninety-two percent (252 patients) had New York Heart Association class III or IV functional status before operation and 25 underwent emergency operation. Valves were harvested under sterile conditions and kept in nutrient medium 199. Freehand (subcoronary) technique was use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
110
2
4

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(119 citation statements)
references
References 18 publications
3
110
2
4
Order By: Relevance
“…In our study, we compared the L-Hydro group with a control group of "in fresh" homografts with the immediate use, real "homovital" grafts. We proceeded like this in order to have a reference comparison with the "gold standard" of the grafts, once the published clinical studies using "homovital" grafts show exceptional results, reaching up to 97% of the grafts free of degeneration in 10 years [22]. In the series of Yacoub, the clinical use of "homovital" homografts was an independent factor for reduced mortality [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, we compared the L-Hydro group with a control group of "in fresh" homografts with the immediate use, real "homovital" grafts. We proceeded like this in order to have a reference comparison with the "gold standard" of the grafts, once the published clinical studies using "homovital" grafts show exceptional results, reaching up to 97% of the grafts free of degeneration in 10 years [22]. In the series of Yacoub, the clinical use of "homovital" homografts was an independent factor for reduced mortality [22].…”
Section: Discussionmentioning
confidence: 99%
“…We proceeded like this in order to have a reference comparison with the "gold standard" of the grafts, once the published clinical studies using "homovital" grafts show exceptional results, reaching up to 97% of the grafts free of degeneration in 10 years [22]. In the series of Yacoub, the clinical use of "homovital" homografts was an independent factor for reduced mortality [22]. It is known that any processing of grafts, including sterilization with low concentration of antibiotics has the potential to alter the viability as well as the physical and antigenic properties of the tissue [23].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies confirmed this observation. Yacoub et al [15] reported their 14-year experience using "homovital" homografts and demonstrated that 89% were free from dysfunction at 10 years of evolution. According to these authors an estimated 73% would be free of dysfunction after 10 years of follow-up for a 15-year-old patient at the time of implant and 97% for a 70-year-old patient.…”
Section: Discussionmentioning
confidence: 99%
“…Homografts can be an alternative for the young women at childbearing age. There is no evident data about the possible complications of this valve not needing an anticoagulation and its generation during pregnancy (Yacoub, 1995;Waszyrowski, 1997). However, some studies in the literature gave an idea.…”
Section: Wwwintechopencommentioning
confidence: 99%